A new comprehensive oral health literacy scale: development and psychometric evaluation - Yue Sun; Jing Sun; Yan Zhao; Aixiao Cheng; Junhong Zhou (BMC, 2021)
Abstract Background It has been widely accepted that oral health status is related to oral health literacy. The need to measure oral health literacy has led to the development of measurement instruments. This study aimed to develop a comprehensive instrument for adults and to examine its reliability and validity in China. Methods A three-step design process was used. First, a literature review and expert panel discussion were used to draw up a 37-item pool covering oral health knowledge, belief, practice, skill, and functional oral health literacy. The Delphi method was used to delete and modify questions in the item pool. The draft instrument was evaluated by nine experts and the consensus among them was calculated using the content validity index. The scale was then used to conduct a psychometric study among 370 participants from community health centers in Beijing. Construct validity, discriminant validity and concurrent validity were examined. The Cronbach's alpha coefficient, and test-retest methods were used to assess reliability. Results The final scale included 30 items across four dimensions. The item-level content validity index was 0.90. Exploratory factor analysis extracted four fixed factors, and the result of the Kaiser-Meyer-Olkin and Bartlett's tests was 0.752, with the model explaining 35.21% of the total variance. The four dimensions were associated with oral health knowledge, perceptions of oral health issues, oral health practice and skills, and functional oral health literacy. The mean score of the lowest 27% was significantly lower than the highest 27% (P < 0.01), suggesting adequate discriminant validity. The associations between comprehensive oral health literacy scores and educational level, income and self-reported literacy level were significant (P < 0.001), showing adequate overall concurrent validity. Internal consistency and test-retest reliability were acceptable, with a Cronbach's alpha of 0.72 and a total test-retest reliability coefficient of 0.979. Conclusions Initial testing of the comprehensive oral health literacy instrument suggested that it is a valid and reliable instrument to evaluate individuals' oral health literacy, with four dimensions for evaluating knowledge, belief, skills, and functional oral health literacy.